Shackleford Banks: Applying Archaeological and Geospatial Approaches to Maritime Settlement and Abandonment - Ellis, Kendra (East Carolina University, 2023)
Shackleford Banks, North Carolina is a 14.5-kilometer barrier island that has not been permanently inhabited by humans in over a century. Before it was abandoned in the beginning of the 20th century, this island had been occupied since at least the mid-eighteenth century by European colonists. These "Ca'e Bankers" lived, not necessarily in isolation, but in self-reliant communities that used their environment to their advantage. They were able to survive by using what the landscape supplied them through oystering, clamming, whaling, porpoise hunting, crabbing, farming, and salvage activities. This project uses archaeological evidence collected from East Carolina University's 2021 summer field school as well as census records, oral histories, and shoreline data to explore the settlement and abandonment of Shackleford Banks communities. Examining this evidence, this thesis looks to find the degree to which economic and environmental change led to the establishment of non- Indigenous settlement on Shackleford Banks, how these communities developed, and what led to their decline and ultimate exodus from the area.
Keywords: whaling; shore-whaling; GIS; surface surveys; maritime history; Navigation--North Carolina--Shackleford Banks--History; Shackleford Banks (N.C.)--History; Barrier islands--North Carolina--Shackleford Banks--History; Coastal archaeology--North Carolina--Shackleford Banks--History; Geospatial data--North Carolina--Shackleford Banks